1983
DOI: 10.2307/1590198
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Heterophil/Lymphocyte Ratio as a Measure of Stress in Chickens

Abstract: The number of lymphocytes in chicken blood samples decreased and the number of heterophils increased in response to stressors and to increasing levels of corticosterone in the chicken feed. The ratio of heterophils to lymphocytes was less variable than the number of heterophil or lymphocyte cells, and the range of values for this ratio was greater than the range of values for heterophils and lymphocytes among control and experimental groups. The heterophil/lymphocyte ratio appears to be a more reliable indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
645
8
23

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,257 publications
(710 citation statements)
references
References 8 publications
34
645
8
23
Order By: Relevance
“…El-Lethey et al, 2000;Wall et al, 2004;Shini et al, 2008). As suggested by Gross and Siegel (1983), H/L ratios of about 0.20, 0.50 and 0.80 are characteristic of low, optimal and high degrees of stress. Our results indicated that hens in this study did not experience severe stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…El-Lethey et al, 2000;Wall et al, 2004;Shini et al, 2008). As suggested by Gross and Siegel (1983), H/L ratios of about 0.20, 0.50 and 0.80 are characteristic of low, optimal and high degrees of stress. Our results indicated that hens in this study did not experience severe stress.…”
Section: Discussionmentioning
confidence: 99%
“…Under practical farm conditions, higher antibody titres in response to vaccines are reported in laying hens placed in floor pens as compared with FC (Shini, 2003). Furthermore, heterophil to lymphocyte (H/L) ratio has been widely used as a sensitive indicator of long-term stress related to immune function in laying hens (Gross and Siegel, 1983;Maxwell and Robertson, 1998), and has been employed as an index of hen welfare (Nicol et al, 2009). However, little is known about the longterm effects of early rearing environment on immune responses in hens housed in FC during the laying period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hematology values in nesting females from this study were similar to values in nesting females from Gabon (Deem et al, 2006). Leukocytosis characterized by heterophilia, lymphopenia, monocytosis, and an elevated heterophil to lymphocyte ratio can be an indicator of physiologic stress response in reptiles (Gross and Siegel, 1983), which could explain the elevations seen in captured foraging turtles relative to nesting turtles. Differences in hematology also might reflect variability in methods and laboratory personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental contaminants, such as insecticides (Mandal et al 1986), crude oil (Leighton 1986), and some organochlorines (Grasman et al 2000), have been found to stimulate a relative heterophilia in birds, but findings are variable. Some studies report depressed (Gross and Siegel 1983) or no effect (Grasman et al 2000) on heterophil numbers in exposed birds.…”
Section: Discussionmentioning
confidence: 99%